Homeownership conceptual framework for urban livability - Elia Syarafina Abdul Shakur; Ahmad Fariz Mohamed; Abdul Samad Abdul Hadi (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
House is a basic need for individuals and families. Difficulty in owning a house has always been one of the major issues debated by the government, people and private sectors in Malaysia. Current economic conditions have made house purchasing almost impossible to many people due to drastic increases of house prices since 2000. The increases was influenced by macro and micro factors based on demand and supply of houses. Among them are migration of rural population to urban areas that leads to increasing demand for owning and renting a house. Hence, developers and investors have taken this migration process to their advantage by increasing their housing and rental prices to gain more profit. With the increase of home values, homeowners were also burdened with rising costs of maintenance which includes assessment of property tax, costs of maintenance and service. The increasing of house prices and the cost of home ownership will affect the population livability in the city. A conceptual framework has been developed. First, to identify the parameters that affects the ability of prospective first home buyers for middle-income earners in the home. Second is to evaluate the housing access indicator parameters on affordability of homeowners in reference to population livability in the city. The outcome of this study is the development of capability parameters to own a house and housing access for livability. This study findings highlight important criteria required to ensure home ownership to improve livability of urban community. Finally, the criteria could be used in developing a guideline for the government and developers to comply and support to the need of the National Housing Policy.